Studi Karakteristik Wisatawan Dan Upaya Pengembangan Produk Wisata Tematik Di Pantai Goa Cemara, Pantai Kuwaru, Dan Pantai Pandansimo Baru Kabupaten Bantul - Fian Damasdino (Media Wisata, 2015)
This research is a quantitative research using the survey method. The locations of the research area in the three tourist objects including Goa Cemara Beach, Kuwaru Beach, and Pandansimo Baru Beach. This study aims to analyze the tourist characteristics in the three research locations and to learn how to formulate a plan for the most appropriate tourism products at three locations sights. The approach used to analyze the tourist characteristics is the four elements of market segmentation: geographic, socio-demographic, psychographic, and behavioural.The samples of the research are 156 respondents with a margin of error of 8% done using purposive sampling technique during March to April 2015 in the three research locations. The data collection was taken by questionnaires, observation, and documentation. Once the data is collected and processed with quantitative analysis using statistical tools, frequency distribution, and cross table (crosstabs).The result shows that the geographic characteristics of tourists in the three locations are balanced between tourists from outside and inside Bantul Regency. Then, the socio-demographic characteristics of tourists in Goa Cemara Beach and Pandansimo Baru Beach are dominated by private employees/BUMN(state-owned corporation), aged 22-60 years old, married and repeater tourist, while tourists in Kuwaru Beach are dominated by students, under 22 years old, single status and first comer tourists.Furthermore, in terms of psychographics, tourists in the three locations who have psychometric characteristics prefer to get something plural, popular, and like to do common activities with the frequency of short stay visits. Lastly, the behaviour of tourists in the three research locations is dominated by doing recreation or having leisure time to enjoy the main attractions of the coastal landscape. The results of tourist characteristics of these three locations are used as the basis for planning of thematic tourism products in accordance with the character of the three research objects